MENINGKATKAN HASIL BELAJAR MATEMATIKA MELALUI MODEL PEMBELAJARAN KOOPERATIF TIPE TEAM ASSISTED INDIVIDUALIZATION - Darminto; Sugeng Riyadi; Awatif (Hiradika | Hira Institute, 2025)
The initial basis of the research was carried out because of the low mathematical scores of students, which was caused by the lack of student motivation in learning because learning still used the lecture method. The study aims to describe the results of learning mathematics using the Cooperative Learning Model Type Team Assisted Individualization (TAI) at SMPN Negeri 23 Merangin Academic Year 2024/2025. This study uses classroom action research (CAR) which was carried out for 2 cycles, each cycle 3 meetings, the research sample was 31 students of class VIII B SMPN Negeri 23 Merangin and focused on learning outcomes and student activities in class. The results of the study showed that in the pre-cycle, 35% (11 people) achieved the specified KKTP, which was ≥75, after implementing the Cooperative method type Team Assisted Individualization (TAI), the student's grades obtained increased, in the first cycle an increase was obtained to 74.20% (23 people), because it had not reached the KKTP so it was declared incomplete. The research continued in cycle II and obtained mathematics learning outcomes of 87.09% (27 students) who completed the learning according to the KKTP. For student activity, the percentage increased from 71% to 83%, an increase of 12%. From these results, the Cooperative Model of the Team Assisted Individualization type was proven to increase grades, especially in class VIII A of SMP Negeri 23 Merangin.